CTCF Regulates Kaposi's Sarcoma-Associated Herpesvirus Latency Transcription by Nucleosome Displacement and RNA Polymerase Programming - Kang, Hyojeung (American Society for Microbiology, 2013)
CCCTC-binding factor (CTCF) has been implicated in various aspects of viral and host chromatin organization and transcriptional control. We showed previously that CTCF binds to a cluster of three sites in the first intron of the Kaposi's sarcoma-associated herpesvirus (KSHV) multicistronic latency-associated transcript that encodes latency-associated nuclear antigen (LANA), viral cyclin (vCyclin), vFLIP, viral microRNAs, and kaposin. We show here that these CTCF binding sites regulate mRNA production, RNA polymerase II (RNAPII) programming, and nucleosome organization of the KSHV latency transcript control region. We also show that KSHV bacmids lacking these CTCF binding sites have elevated and altered ratios of spliced latency transcripts. CTCF binding site mutations altered RNAPII and RNAPII-accessory factor interactions with the latency control region. CTCF binding sites were required for the in vitro recruitment of RNAPII to the latency control region, suggesting that direct interactions between CTCF and RNAPII contribute to transcription regulation. Histone modifications in the latency control region were also altered by mutations in the CTCF binding sites. Finally, we show that CTCF binding alters the regular phasing of nucleosomes in the latency gene transcript and intron, suggesting that nucleosome positioning can be an underlying biochemical mechanism of CTCF function. We propose that RNAPII interactions and nucleosome displacement serve as a biochemical basis for programming RNAPII in the KSHV transcriptional control region.